2022
DOI: 10.1111/wvn.12563
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of perception of barriers and facilitators to chronic disease self‐management among older adults: Implications for evidence‐based practice

Abstract: Background:An aging population has contributed to an increased prevalence in chronic disease. To empower patients, healthcare systems are shifting toward chronic disease self-management. However, no review on how older adults self-manage chronic disease and the barriers and facilitators they experience has been published. Aims:To explore barriers and facilitators perceived by older adults during the process of self-managing chronic disease.Methods: A systematic review of qualitative literature was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The impact of healthcare-quality experiences on dementia risk may be due in part to giving inadequate training to healthcare professionals in providing personalized recommendation plans for addressing the health priorities of patients, including dementia prevention. 20 A quasi-experimental study found that when physicians gave a personalized recommendation plan for managing dementia risk factors, it lowered the risk of developing dementia, compared to usual care. 21 However, only 5% of people 55 to 64-years-old in the United States report that a physician has discussed dementia prevention with them.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of healthcare-quality experiences on dementia risk may be due in part to giving inadequate training to healthcare professionals in providing personalized recommendation plans for addressing the health priorities of patients, including dementia prevention. 20 A quasi-experimental study found that when physicians gave a personalized recommendation plan for managing dementia risk factors, it lowered the risk of developing dementia, compared to usual care. 21 However, only 5% of people 55 to 64-years-old in the United States report that a physician has discussed dementia prevention with them.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of healthcare-quality experiences on dementia risk may be due in part to giving inadequate training to healthcare professionals in providing personalized recommendation plans for addressing the health priorities of patients, including dementia prevention. 19 A quasiexperimental study found that when physicians gave a personalized recommendation plan for managing dementia risk factors, it lowered the risk of developing dementia, compared to usual care. 20 Only 5% of people 55 to 64-years-old in the U.S. report that a physician has discussed dementia prevention with them.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic health conditions, such as cardiovascular diseases, diabetes, respiratory disorders, and mental health conditions, continue to pose significant challenges and affect millions of individuals worldwide. 1 , 2 The prevalence of chronic conditions is increasing due to factors such as aging populations, sedentary lifestyles, unhealthy diets, and environmental influences. 3 , 4 These conditions not only have a profound impact on the affected individuals, but also place a considerable burden on healthcare systems, economies, and society as a whole.…”
Section: Introductionmentioning
confidence: 99%